Hemophagocytic lymphohistiocytosis: a review inspired by the COVID-19 pandemic - ATAGÜNDÜZ, IŞIK (SPRINGER HEIDELBERG, 2021)
Hemophagocytic syndrome (HPS) or hemophagocytic lymphohistiocytosis (HLH) is an acute and rapidly progressive systemic inflammatory disorder characterized by cytopenia, excessive cytokine production, and hyperferritinemia. Common clinical manifestations of HLH are acute unremitting fever, lymphadenopathy, hepatosplenomegaly, and multiorgan failure. Due to a massive cytokine release, this clinical condition is considered as a cytokine storm syndrome. HPS has primary and acquired (secondary, reactive) forms. Its primary form is mostly seen in childhood and caused by various mutations with genetic inheritance and, therefore, is called familial HLH. Secondary HLH may be caused in the presence of an underlying disorder, that is, secondary to a malignant, infectious, or autoimmune/autoinflammatory stimulus. This paper aims to review the pathogenesis and the clinical picture of HLH, and its severe complication, the cytokine storm, with a special emphasis on the developed classification criteria sets for rheumatologists, since COVID-19 infection has clinical symptoms resembling those of the common rheumatologic conditions and possibly triggers HLH. MED-LINE/Pubmed was searched from inception to April 2020, and the following terms were used for data searching: hemophagocytic syndrome OR macrophage activation syndrome OR hemophagocytic lymphohistiocytosis, OR cytokine storm. Finally, AND COVID-19 was included in this algorithm. The selection is restricted to the past 5 years and limited numbers of earlier key references were manually selected. Only full-text manuscripts, published in an English language peer-reviewed journal were included. Manuscript selection procedure and numbers are given in Fig. 2. Briefly, the database search with the following terms of Hemophagocytic syndrome OR Macrophage activation syndrome OR Hemophagocytic lymphohistiocytosis OR Cytokine storm yielded 6744 results from inception to April 2020. The selection is restricted to the past 5 years and only limited numbers of earlier key references were selected, and this algorithm resulted in 3080 manuscripts. The addition of (AND COVID-19) resulted in 115 publications of which 47 studies, together with four sections of an online book were used in the final review. No statistical method was used. HLH is triggered by genetic conditions, infections, malignancies, autoimmune-autoinflammatory diseases, and some drugs. In COVID-19 patients, secondary HLH and cytokine storm may be responsible for unexplained progressive fever, cytopenia, ARDS, neurological and renal impairment. Differentiation between the primary and secondary forms of HLH is utterly important, since primary form of HLH requires complicated treatments such as hematopoietic stem cell transplantation. Further studies addressing the performance of HScore and other recommendations in the classification of these patients is necessary.
Keywords: Hemophagocytic syndrome; Hemophagocytic lymphohistiocytosis; Macrophage activation syndrome; Cytokine storm syndrome; MACROPHAGE ACTIVATION SYNDROME; JUVENILE IDIOPATHIC ARTHRITIS; CLINICAL-FEATURES; DIAGNOSIS; ADULT; SCORE; PATHOPHYSIOLOGY; PATHOGENESIS; VALIDATION; CYTOKINES